Vector control in primary health care - WHO Scientific Group on Vector Control in Primary Health Care; World Health Organization (Geneva : World health Organization, 1987)
Presents technical information and practical advice concerning use of the primary health care approach to reduce the transmission of vector-borne diseases. In view of the striking prevalence of these diseases and the correspondingly high costs o control, the book advocates the use of simple control measures that are affordable as well as reliable and effective. The importance of mobilizing community resources is repeatedly emphasized. A brief description of projects that have successfully used this approach is followed by an outline of the different vector species that qualify as suitable targets for community-based control efforts. Appropriate species include malaria vectors, vectors of arboviral diseases, vectors of African trypanosomiasis, vectors of Chagas disease, vectors of liceborne typhus, rodents as reservoirs of disease, and cyclops as intermediate hosts of dracunculiasis. Of particular practical value is a discussion of different vector control measures, including several very new techniques, that are suitable for use at the community level. All these measures, whether involving the use of locally constructed insect traps or head-bands and soaps containing repellents, share the advantages of simplicity, low cost, and feasibility for use at the community level
Introduction -- 1. The integration of vector control into primary health care -- 2. Delivery of vector control through primary health care -- 3. Communication and epidemiology -- 4. Suitability of various vector control measures for primary health care -- 5. Human resources needs and development -- Research requirements for vector control through primary health care -- 7. Recommendations -- Acknowledgements -- References
Keywords: Disease Vectors; Pest Control; Primary Health Care; Communicable Diseases and their Control